2019
DOI: 10.3390/ijms20081859
|View full text |Cite
|
Sign up to set email alerts
|

Kojyl Cinnamate Ester Derivatives Increase Adiponectin Expression and Stimulate Adiponectin-Induced Hair Growth Factors in Human Dermal Papilla Cells

Abstract: Adiponectin (APN), released mainly from adipose tissue, is a well-known homeostatic factor for regulating glucose levels, lipid metabolism, and insulin sensitivity. A recent study showed that human hair follicles express APN receptors and the presence of APN-mediated hair growth signaling, thereby suggesting that APN is a potent hair growth-promoting adipokine. Previously, kojyl cinnamate ester derivatives (KCEDs) were synthesized in our institute as new anti-aging or adiponectin-/adipogenesis-inducing compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Adiponectin mainly plays its role through adiponectin receptors 1 and 2 (AdipoRs 1 & 2) (Wang et al., 2017; Yamauchi et al., 2014; Yang et al., 2018). Dietary fatty acid composition and excessive deposition of body fat can affect adiponectin secretion and AdipoR 1 & 2 expression, and then affect lipid metabolism and energy metabolism (Geng et al., 2016; Holland et al., 2017; Park & Cho, 2019; Sobolesky et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin mainly plays its role through adiponectin receptors 1 and 2 (AdipoRs 1 & 2) (Wang et al., 2017; Yamauchi et al., 2014; Yang et al., 2018). Dietary fatty acid composition and excessive deposition of body fat can affect adiponectin secretion and AdipoR 1 & 2 expression, and then affect lipid metabolism and energy metabolism (Geng et al., 2016; Holland et al., 2017; Park & Cho, 2019; Sobolesky et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Park et al report that kojyl cinnamate ester derivatives and Seletinoid G promote adiponectin secretion by human follicular dermal papilla cells. In addition, cell medium containing secreted adiponectin induces the expression of hair growth-related factors, thus suggesting an involvement of the hormone in the promotion of hair growth in humans [14]. Finally, Okura et al investigate the interaction between adiponectin and NGFβ and SPARC.…”
mentioning
confidence: 99%
“…Recently, the rates of hair loss among adults are on the rise, and limited treatment options are available for such patients 25,26 . Most studies confirmed that the dermal papilla cells (DPCs) cause ageing of hair follicles 27,28 . With age, the hair follicle becomes old, and the mitotic capacity of cells worsen.…”
Section: Discussionmentioning
confidence: 99%